The Motif of Lovesickness in the Acts of Paul and Thecla and the Acts of Andrew - Cobb, Christy (Wake Forest University, 2010)
This thesis explores the literary motif of lovesickness in two early Christian ascetic texts - the Acts of Paul and Thecla and the Acts of Andrew. In order to argue that the authors of these texts utilized lovesickness as a motif, I contextualize the illness in contemporaneous literature including medical texts, Greek poetry and literature, and ancient Greek novels. After showing that lovesickness was a concern in this literature, I engage in an exegetical reading of the Acts of Paul and Thecla and the Acts of Andrew. I suggest that the astute reader might have recognized the symptoms of lovesickness in these sections of the Apocryphal Acts because of the inclusion and utilization of this motif in contemporaneous literature. Furthermore, I argue that these Christian authors intentionally used lovesickness as a narrative strategy to eroticize the relationship between the follower and the apostle. I note that the symptoms of lovesickness are experienced only by the follower, and not by the apostle, making the relationship uni-directional. Therefore, this thesis identifies a motif of lovesickness in the Apocryphal Acts and argues that this motif functions to elevate the status of the apostle within the narrative.
Keywords: Lovesickness; Apocryphal Acts of the Apostles; Acts of Paul; Acts of Andrew; Early Christian Literature; Thecla